2022
DOI: 10.3390/antiox11112246
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Microwave-Assisted Sargassum fusiforme Extracts with Improved Antioxidant Activity Using Hybrid Response Surface Methodology and Artificial Neural Networking-Genetic Algorithm

Abstract: Sargassum fusiforme (SF) is a popular edible brown macroalga found in Korea, Japan, and China and is known for its health-promoting properties. In this study, we used two sophisticated models to obtain optimized conditions for high antioxidant activity and metabolite profiling using high-resolution mass spectrometry. A four-factor central composite design was used to optimize the microwave-assisted extraction and achieve the maximum antioxidant activities of DPPH (Y1: 28.01 % inhibition), ABTS (Y2: 36.07 % inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…During development, the input layer was not triggered using the transfer function, but the output and hidden layers were activated using pure line (purelin) and tangent sigmoid transfer (tansig) functions in MATLAB. In the experiment, the lowest feasible error between training and testing was evaluated, and the minimum number of epochs to prevent model overfitting was considered; the results were consistent with the findings of previous works [ 32 ]. Training the network with the Levenberg–Marquardt technique yielded the best validation performance for all dependent variables: TPC (Y 1 ), TFC (Y 2 ), DPPH (Y 3 ), and CUPRAC (Y 4 ) ( supplementary data Figures S1–S4 ).…”
Section: Resultssupporting
confidence: 81%
“…During development, the input layer was not triggered using the transfer function, but the output and hidden layers were activated using pure line (purelin) and tangent sigmoid transfer (tansig) functions in MATLAB. In the experiment, the lowest feasible error between training and testing was evaluated, and the minimum number of epochs to prevent model overfitting was considered; the results were consistent with the findings of previous works [ 32 ]. Training the network with the Levenberg–Marquardt technique yielded the best validation performance for all dependent variables: TPC (Y 1 ), TFC (Y 2 ), DPPH (Y 3 ), and CUPRAC (Y 4 ) ( supplementary data Figures S1–S4 ).…”
Section: Resultssupporting
confidence: 81%
“…The literature showed that phenolic acids lose certain fragments such as methyl (15 Da), hydroxyl (18 Da), and carboxyl (44 Da) during the collision, which helped in determining the compounds [ 3 ]. Compounds 1 – 14 have been tentatively identified in Sargassum fusiforme based on previously reported fragmentation behavior data ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 ]. Interestingly, 5-(3′,5′-Dihydroxyphenyl)-γ-valerolactone 3- O -glucuronide and coumaroylquinic acid were tentatively acknowledged for the first time in optimized MUAE SH extract.…”
Section: Resultsmentioning
confidence: 99%
“…However, butanediol lignans generate [M–H-48] ions by breaking at the β-position as a combined loss of CHO and H 2 O from the diol structure [ 24 , 25 ]. Based on the monoisotopic mass [M–H]–, fragmentation behavior in mass spectroscopy, and previous studies, compounds 29 – 33 were recognized as lignan molecules and previously reported in Sargassum sp., Ecklonia sp., and sea vegetables [ 15 , 16 , 17 , 19 ]. Among lignans, compounds 32 and 33 were tentatively reported for the first time in the SH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their positive effects on human health have thus far undergone substantial study. The study of polyphenolic compounds is gaining popularity, and the first and most crucial stage in extracting and purifying polyphenolic compounds from plant sources is extraction [ 4 ], given that the extraction of polyphenol is influenced by several factors, including the chemical makeup of the sample, the solvent employed, agitation, extraction time, solute/solvent ratio, and temperature [ 5 , 6 ]. Furthermore, phenolic molecules should not be oxidized because they participate in the enzymatic browning reaction and lose their phenol activity and antioxidant capacity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%